2008
DOI: 10.1007/s11814-008-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-substrate on anaerobic slurry phase bioremediation of TNT-contaminated soil

Abstract: Molasses and starch were used to estimate the effect of co-substrate on anaerobic slurry phase bioremediation of TNT (2,4,6-trinitrotoluene)-contaminated soil. Degradation efficiency of TNT in molasses and starch addition was approximately 97% and 87%, which is 50-60% higher than 38% without co-substrate addition. Molasses and starch addition enhanced TNT degradation. It was proved that the TNT degradation was a mainly biological process from the result of an abiotic control experiment. In case of molasses add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This includes supplemental carbon and nitrogen sources [31][32][33][34][35], microorganism [36], pH and temperature [32,36] in aqueous phase as well as slurry concentration, agitation speed [28] and surfactant [29,37] in slurry phase. Nevertheless, a one at a time approach was used to look at the effect of each factor in slurry phase and therefore the possible interactions among the effective factors have not yet been assessed.…”
Section: Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes supplemental carbon and nitrogen sources [31][32][33][34][35], microorganism [36], pH and temperature [32,36] in aqueous phase as well as slurry concentration, agitation speed [28] and surfactant [29,37] in slurry phase. Nevertheless, a one at a time approach was used to look at the effect of each factor in slurry phase and therefore the possible interactions among the effective factors have not yet been assessed.…”
Section: Trialmentioning
confidence: 99%
“…Previous studies have shown that carbon and nitrogen sources are essential for TNT metabolism [31][32][33][34][35] since cultures deficient in these two sources could not grow [31]. Boopathy et al [31] and Kalafut et al [35] have shown that NH 4 Cl can serve as a suitable nitrogen source in aqueous phase.…”
Section: Screening Experimentsmentioning
confidence: 99%
“…In treatments T4 and T5, 1.5 g of KNO 3 was added as a nitrogen source and electron acceptor. Molasses was applied in the treatments T3 and T4 in single-doses at the start of the experiment (In et al 2008). These experiments were conducted for 30 days and the concentrations of DDT were measured (USEPA SW-846 2007; USEPA SW-846 1996a; USEPA SW-846 1996b) at the beginning and end of each treatment.…”
Section: Microcosm Setupsmentioning
confidence: 99%
“…Studies have shown that TNT is susceptible to biotransformation under aerobic and anaerobic conditions (Esteve-Nunez et al, 2001;In et al, 2008). This susceptibility to biological (microbial) degradation can be exploited for decontamination purposes.…”
Section: Introductionmentioning
confidence: 99%